2012
DOI: 10.1002/per.832
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Events and Temperament Change during Early and Middle Adolescence: The TRAILS Study

Abstract: This project investigates how stressful events are related to deviations from normative temperament development during adolescence. Temperament traits were assessed at ages 11 and 16 years. Life-event data was captured using an interview (total n = 1197). Normative changes were found in all traits. A linear trend was found between the experience of stressful events and temperament development. Adolescents exposed to stressful events showed smaller decreases in fear and shyness, stronger decreases in effortful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 41 publications
13
82
2
Order By: Relevance
“…A range of evidence indicates that dispositional negativity can be increased by stress, trauma, and negative life events (e.g., death of a spouse, birth of a child, chronic disease; Barlow et al, 2013; Hutteman, Bleidorn, Kerestes, et al, 2014; Jeronimus, Riese, Sanderman, & Ormel, 2014; Jokela, Hakulinen, Singh-Manoux, & Kivimaki, 2014; Jokela, Kivimaki, Elovainio, & Keltikangas-Jarvinen, 2009; Laceulle, Nederhof, Karreman, Ormel, & Van Aken, 2011; Ludtke, Roberts, Trautwein, & Nagy, 2011; Parker, Ludtke, Trautwein, & Roberts, 2012; Roberts, Caspi, & Moffitt, 2003; Robins, Caspi, & Moffitt, 2002). But importantly it can also be decreased by cognitive-behavioral (Barlow et al, 2013; Bennett et al, 2015; Mihalopoulos et al, 2015) and pharmacological interventions for anxiety and depression (Barlow et al, 2013; Soskin, Carl, Alpert, & Fava, 2012), raising the possibility of developing strategies for identifying high-risk individuals and preventing the onset of more severe sequelae.…”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
“…A range of evidence indicates that dispositional negativity can be increased by stress, trauma, and negative life events (e.g., death of a spouse, birth of a child, chronic disease; Barlow et al, 2013; Hutteman, Bleidorn, Kerestes, et al, 2014; Jeronimus, Riese, Sanderman, & Ormel, 2014; Jokela, Hakulinen, Singh-Manoux, & Kivimaki, 2014; Jokela, Kivimaki, Elovainio, & Keltikangas-Jarvinen, 2009; Laceulle, Nederhof, Karreman, Ormel, & Van Aken, 2011; Ludtke, Roberts, Trautwein, & Nagy, 2011; Parker, Ludtke, Trautwein, & Roberts, 2012; Roberts, Caspi, & Moffitt, 2003; Robins, Caspi, & Moffitt, 2002). But importantly it can also be decreased by cognitive-behavioral (Barlow et al, 2013; Bennett et al, 2015; Mihalopoulos et al, 2015) and pharmacological interventions for anxiety and depression (Barlow et al, 2013; Soskin, Carl, Alpert, & Fava, 2012), raising the possibility of developing strategies for identifying high-risk individuals and preventing the onset of more severe sequelae.…”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%
“…Indeed, mean levels of dispositional negativity show substantial fluctuations—equivalent to T -scores of 2 in males and 5 in females—between the ages of 10 and 65, peaking in adolescence (Soto, John, Gosling, & Potter, 2011). A range of evidence shows that dispositional negativity can be increased by exposure to stress or trauma in adolescence and adulthood (Barlow et al, 2013; Jeronimus, Riese, Sanderman, & Ormel, 2014; Jokela, Hakulinen, Singh-Manoux, & Kivimaki, 2014; Jokela, Kivimaki, Elovainio, & Keltikangas-Jarvinen, 2009; Laceulle, Nederhof, Karreman, Ormel, & Van Aken, 2011; Ludtke, Roberts, Trautwein, & Nagy, 2011; Parker, Ludtke, Trautwein, & Roberts, 2012; Roberts, Caspi, & Moffitt, 2003; Robins, Caspi, & Moffitt, 2002). For example, exposure to more frequent negative life events (e.g., death of an immediate family member or friend, academic expulsion, running away) between the ages of 11 and 16 is associated with elevated levels of dispositional negativity in Dutch adolescents ( n = 1,197; Laceulle et al, 2011).…”
Section: Elevated Dispositional Negativity Confers Heightened Risk Fomentioning
confidence: 99%
“…Van Leeuwen et al (2004b), for example, demonstrated that parental behavior moderated the relationship between a child's personality and the level of problem behavior, suggesting that disagreeable children are especially at risk to develop problem behavior when parents act in a negative controlling way. Laceulle et al (2012) showed that stressful events moderated normative personality development in adolescence. The same contexts may also moderate Path 4, impacting direct biological influences on characteristic manifestations (Paths 7b).…”
Section: De Fruyt · De Clercqmentioning
confidence: 99%